Mapping time :Powerpoint - Kraak, M.J. (University of Twente, 2020)
This lecture presents: Mapping time: Alexandre Javakhishvili; The story of Alexandre Javakhishvili; Tornado’s in the US; Traffic intensity in New York City; Perception of time; Types of time; Event; Spatio-temporal data; Change of object.